Penerapan Metode Desain Pembelajaran di Era Pandemi oleh Guru Sekolah MI Al- Irsyad - Fitroh, Aulia; Fadilah, Diah Kurniawati; Mardiyanto, Muhammad Sodiq (Lembaga Yasin AlSys, 2022)
The spread of the Covid-19 virus pandemic in Indonesia has resulted in schools stopping a face-to-face learning process. This learning is done by distance learning or learning from the homes of each student. This online and distance learning requires the help of capable and easily accessible technology. The 4.0 revolution is the right learning program, which can be applied today with the aim of addressing technology and educational progress. The purpose of this study was to find out how the learning design system at the MI Al - Irsyad school in the 2020 Corona Pandemic situation until now.